French Motorcyclists and the 80 km/hr Speed Limit: Conditionality and Risk-Taking with Regard to Age, Type and Power of Motorbike - Gaymard, Sandrine; Tiplica, Teodor; Schvartz, Anne-Sophie (Mediterranean Journal of Social Sciences, 2021)
After months of controversy, the speed limit on two-way secondary French roads without a median strip was reduced from 90 to 80 km/hr on 1 July 2018. Thousands of car drivers and motorcyclists have since protested against this measure, and the present study concerned the latter group. Starting from the Theory of Conditionality in the field of social thinking, which holds that prescriptions are massively conditional, a specific questionnaire based on 23 conditional scripts has been devised. A total of 661 male motorcyclists were asked about the conditions justifying the transgression of the 80 km/hr limit. Results showed that those motorcyclists who exceeded this limit did so by at least by 20 km/hr. A personalized assessment of speed, the pleasure associated with driving, and good road and weather conditions were the most conditional situations, while situations linked to the risk of loss of control were the least conditional. This study suggests that the determinants of risk-taking must be studied at the group and context levels, and that behavior is influenced by the system of social norms. Although this system may conflict with the Highway Code, it reflects an adaptation of the group linked to a need for meaning. Â  Received: 7 July 2021 / Accepted: 12 August 2021 / Published: 5 September 2021